PSTPIP2 inhibits cisplatin-induced acute kidney injury by suppressing apoptosis of renal tubular epithelial cells - Zhu, Hong (Cell Death Dis, 2020)
Cisplatin (CP) is an effective chemotherapeutic agent widely used in the treatment of various solid tumours. However, CP nephrotoxicity is an important limitation for CP use; currently, there is no method to ameliorate cisplatin-induced acute kidney injury (AKI). Recently, we identified a specific role of proline–serine–threonine phosphatase-interacting protein 2 (PSTPIP2) in cisplatin-induced AKI. PSTPIP2 was reported to play an important role in a variety of diseases. However, the functions of PSTPIP2 in experimental models of cisplatin-induced AKI have not been extensively studied. The present study demonstrated that cisplatin downregulated the expression of PSTPIP2 in the kidney tissue. Administration of AAV-PSTPIP2 or epithelial cell-specific overexpression of PSTPIP2 reduced cisplatin-induced kidney dysfunction and inhibited apoptosis of renal tubular epithelial cells. Small interfering RNA-based knockdown of PSTPIP2 expression abolished PSTPIP2 regulation of epithelial cell apoptosis in vitro. Histone acetylation may impact gene expression at the epigenetic level, and histone deacetylase (HDAC) inhibitors were reported to prevent cisplatin-induced nephrotoxicity. The UCSC database was used to predict that acetylation of histone H3 at lysine 27 (H3K27ac) induces binding to the PSTPIP2 promoter, and this prediction was validated by a ChIP assay. Interestingly, an HDAC-specific inhibitor (TSA) was sufficient to potently upregulate PSTPIP2 in epithelial cells. Histone acetylation-mediated silencing of PSTPIP2 may contribute to cisplatin nephrotoxicity. PSTPIP2 may serve as a potential therapeutic target in the prevention of cisplatin nephrotoxicity.